2018
DOI: 10.1111/pbi.13024
|View full text |Cite
|
Sign up to set email alerts
|

A metabolome‐based core hybridisation strategy for the prediction of rice grain weight across environments

Abstract: Summary Marker‐based prediction holds great promise for improving current plant and animal breeding efficiencies. However, the predictabilities of complex traits are always severely affected by negative factors, including distant relatedness, environmental discrepancies, unknown population structures, and indeterminate numbers of predictive variables. In this study, we utilised two independent F 1 hybrid populations in the years 2012 and 2015 to predict rice thousand grain wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…A correlation analysis between the observed and predicted BPH-YPPs indicated that the predictability of BPH-YPP for Pop2015 was further improved (Fig 3C; r = 0.44, P = 0.001). Therefore, for predicting component traits (e.g., grain weight) (Dan et al, 2019), the dissection of population structures as the initial step in building predictive models is better than the screening of predictive variables.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A correlation analysis between the observed and predicted BPH-YPPs indicated that the predictability of BPH-YPP for Pop2015 was further improved (Fig 3C; r = 0.44, P = 0.001). Therefore, for predicting component traits (e.g., grain weight) (Dan et al, 2019), the dissection of population structures as the initial step in building predictive models is better than the screening of predictive variables.…”
Section: Resultsmentioning
confidence: 99%
“…Details of the plant materials have been presented previously (Dan et al, 2019). Briefly, two hybrid populations were used to explore predictive models of heterosis for rice grain yield.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, those dysfunctions resulted from the disorders on the transcriptional, post-transcriptional and translational regulations. Many groups have devoted to the plant mitochondrial omics studies, and the interaction between nuclear and mitochondrion has contributed to the speciation and cytoplasmic male sterility which could be applied to explore the crop hybrid vigor [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, these dysfunctions result from disorders of transcriptional, post-transcriptional and translational regulation. Many groups have performed plant mitochondrial omics studies, and the interaction between the nucleus and the mitochondrion has contributed to speciation and cytoplasmic male sterility, which could be applied to explore crop hybrid vigor [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%